Ruptured splenic abscess: a rare case entity - Ayra Suleman; Muhammad Zeeshan Sarwar; Yasin Rafi; Syed Asghar Naqi (Journal of the Pakistan Medical Association, 2022)
Ruptured splenic abscess has been reported as a rare clinical entity in literature. We present the case of a middle aged female with peritonitis due to a ruptured splenic abscess. Emergency splenectomy was done and broad spectrum antibiotic was given postoperatively. However, the patient could not survive and died on the 4th postoperative day. We propose that a ruptured splenic abscess should always be considered in the differential diagnosis of peritonitis, especially in an immunocompromised individual. Key Words: splenic abscess, immunocompromised, splenectomy. Continuous...